Determination of critical load of elastic steel column based on experimental data - Bilyk, Sergii (КНУБА, 2016)
We have developed a general approach for assessing critical-strength for the central-compressed steel elements, what have an initial imperfections. The metod is made on the basis of experimental data. The method is a development of the method Tymoshenko-Southwell. In work we show of the solutions several tasks. We demonstrate the possibility to determine of critical strength for the central-compressed steel elements on the basis of experimental data initial geometric imperfections. The results can be used at checking the technical condition of the Central compressed rod in the survey metal structures trusses, columns, structural designs.
Keywords: steel structures; stability; buckling; steel elements; slenderness; reduction factor for buckling; initial deflection; residual stresses initial imperfections; the critical force; method Tymoshenko-Southwell.; 624.075.23.014.2